Influence of Trinidad Lake Asphalt on the physical and anti-aging properties of petroleum asphalt. (2nd December 2017) - Xu, Song; Hu, Changbin; Yu, Jianying; Liu, Renbing; Zhou, Xinxing
ABSTRACT: The road performance of Trinidad Lake Asphalt (TLA) modified petroleum asphalt (PA) were evaluated. Results show that TLA improves the high temperature performance of PA to avoid rutting resistance, while it degrades the low temperature performance of PA making PA face more risk of cracking. Meanwhile, the influence of TLA on short-term aging performance of PA is slight, but TLA enhances the long-term aging (PAV and UV) resistance, which is favorable for extending lifetime of pavement. According to this investigation, TLA modified asphalt is recommended to be used in warm areas and the optimal addition of TLA is 30 wt.% for the road construction.